The effectiveness of using brainstorming technique in writing narrative text at the XI Grade students of accounting in SMK NEGERI 1 Kota Jambi academic year 2017/2018 - Meilinda Suasana, Wennyta Nurul Fitri (JELT: Journal of English Language Teaching, 2018)
AbstractThe purpose of this research is to know whether there is effectiveness to use brainstorming technique in writing narrative text at the Eleventh Grade Students of Accounting in SMK N 1 Kota Jambi Academic Year 2017/2018. The method apply in conducting this research is quantitative. The population of the research is 160, by using brainstorming technique is gotten the sample 41 students in experimental class and 41 students without using brainstorming technique in control class. To collect the data in this research is using test for the both experimental and control class. From the comparison between experimental and control class is gotten there is a significant different result from writing narrative text by using brainstorming technique and without using brainstorming technique. From the score is gotten the comparison between t table and t test 4,8 > 0,95, it means Ha (alternative hypothesis) is accepted and Ho ( null hypothesis ) is rejected or that is true the using of brainstorming technique in writing narrative text is more effective than without using brainstorming technique.Keywords: Brainstorming technique, Narrative